Investigating late-time dark energy and massive neutrinos in light of DESI Y1 BAO - Rebouças, João [UNESP]; de Souza, Diogo H.F. [UNESP]; Zhong, Kunhao; Miranda, Vivian; Rosenfeld, Rogerio [UNESP] (IOP Publishing, 2025)
Baryonic Acoustic Oscillation (BAO) data from the Dark Energy Spectroscopic Instrument (DESI), in combination with Cosmic Microwave Background (CMB) data and Type Ia Supernovae (SN) luminosity distances, suggests a dynamical evolution of the dark energy equation of state with a phantom phase (w < -1) in the past when the so-called w 0 wa parametrization w(a) = w 0 + w a (1-a) is assumed. In this work, we investigate more general dark energy models that also allow a phantom equation of state. We consider three cases: an equation of state with a transition feature, a model-agnostic equation of state with constant values in chosen redshift bins, and a k-essence model. Since the dark energy equation of state is correlated with neutrino masses, we reassess constraints on the neutrino mass sum focusing on the model-agnostic equation of state. We find that the combination of DESI BAO with Planck 2018 CMB data and SN data from Pantheon, Pantheon+, or Union3 is consistent with an oscillatory dark energy equation of state, while a monotonic behavior is preferred by the DESY5 SN data. Performing model comparison techniques, we find that the w 0 wa parametrization remains the simplest dark energy model that can provide a better fit to DESI BAO, CMB, and all SN datasets than ΛCDM. Constraints on the neutrino mass sum assuming dynamical dark energy are relaxed compared to ΛCDM and we show that these constraints are tighter in the model-agnostic case relative to w 0 wa model by 70%-90%.
Keywords: baryon acoustic oscillations; cosmological neutrinos; dark energy experiments; supernova type Ia - standard candles